Workplace violence against family medicine doctors as part of the global phenomenon in the healthcare sector - Ristić, Dajana (PONS - medicinski časopis, 2022)
Introduction. Violence against healthcare workers is a significant global problem and is prevalent in both developed and underdeveloped countries. In the Republika Srpska, there is also a problem of violence against health workers and it occurs in the public and private health sector. Most attacks come from patients or their family members who have a mental illness or have harmful behavioral habits such as alcohol or drug abuse.Aim. Examine the prevalence of violence at work against family medicine doctors, the most common forms of violence, the consequences of violence on the professional work of doctors, as well as prevention measures.Methods. The research was conducted in 16 health institutions in the Republika Srpska in the period from January to December 2018 according to the type of cross-sectional study on a randomized sample of 287 respondents, doctors who worked in the service of family medicine. The research instrument was a specially created questionnaire that was created for this research, and the obtained data were statistically processed in the program package SPSS v.19. Research results. Doctors of both sexes participated in the research, and the majority of respondents were women, 77,8% of them, while 22,2% were men. The majority of respondents are employed in public health care, 97,11% of them. Of the total number of doctors surveyed, 84,48% of them experienced violence at work during their working life. The analysis of the representation of certain types of violence showed that the most common form of violence is verbal violence in the percentage of 40,7%. A total of 73,62% of respondents believe that violence at work affects further professional work.Conclusion. Violence at work against family medicine doctors in Republika Srpska is significant. The most common forms of violence are verbal violence and rude or disrespectful behavior, and as the most important prevention measures, family medicine doctors point out a lower workload with the number of examinations, the introduction of stricter criminal liability for offenders and the introduction of the status of an official.
Keywords: Violence at work, doctors, family medicine.